2019
DOI: 10.3390/life9010029
|View full text |Cite
|
Sign up to set email alerts
|

The Astrophysical Formation of Asymmetric Molecules and the Emergence of a Chiral Bias

Abstract: The biomolecular homochirality in living organisms has been investigated for decades, but its origin remains poorly understood. It has been shown that circular polarized light (CPL) and other energy sources are capable of inducing small enantiomeric excesses (ees) in some primary biomolecules, such as amino acids or sugars. Since the first findings of amino acids in carbonaceous meteorites, a scenario in which essential chiral biomolecules originate in space and are delivered by celestial bodies has arisen. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 142 publications
(165 reference statements)
1
32
0
Order By: Relevance
“…Not only this, the additional processing by circularly polarised UV radiations in such experiments has been reported to result into enantio‐enrichment of synthesized chiral organic molecules. This further supports the enantiomeric excess of life‐supporting amino acids and sugars observed in astrophysical objects …”
Section: Introductionsupporting
confidence: 79%
“…Not only this, the additional processing by circularly polarised UV radiations in such experiments has been reported to result into enantio‐enrichment of synthesized chiral organic molecules. This further supports the enantiomeric excess of life‐supporting amino acids and sugars observed in astrophysical objects …”
Section: Introductionsupporting
confidence: 79%
“…2014; Garcia et al. 2019). Laboratory experiments simulating presolar and interstellar environments have shown that slight l ‐ or d ‐enantiomeric enrichments of 0.2–2.5% of several chiral amino acids, including alanine, valine, norvaline, leucine, α‐amino‐ n ‐butyric acid, and 2,3‐diaminopropanoic acid, can be produced directly from interstellar ice analogs for a given direction of UV circularly polarized light (UV CPL), while no amino acid asymmetry was induced with non‐polarized UV light (Modica et al.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the synthesis of life's building blocks, Meierhenrich and co-workers showed that exposure of circular polarized light (CPL) in simulated interstellar racemic alanine can induce a chemical imbalance between the formations of L-or D-alanine where the imbalance depends from the wavelength of the incident CPL and sense of rotation [30,31]. Further investigations, performed in simulated conditions, proven that glyceroaldehyde (1, Scheme 1), the first chiral product of the "formose" reaction [32] -one of the chemical pathways for the synthesis of carbohydrates-is present in comets and other space bodies [31]. It is probable that the chemical imbalance between the two possible stereoisomers of 1 occurred before seeding the Earth by asteroids or comets impact [33] creating the conditions for a deracemization before the prebiotic polymerization of peptides and formation of nucleic acids.…”
Section: Prebiotic Scenarios For the Chemical Imbalance Of Amino Acidmentioning
confidence: 99%